Forecasting with maximum entropy : the interface between physics, biology, economics and information theory - Fort, Hugo (IOP (Series). Release 22., 2022)
This book aims at providing a unifying framework, based on Information Entropy and its maximization, to connect the phenomenology of evolutionary biology, community ecology, financial economics, and statistical physics.